2010
DOI: 10.1016/j.ejcts.2009.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic spinal cord malperfusion after stent-graft coverage of the entire descending aorta☆

Abstract: Extensive stent-graft coverage of the entire thoracic aorta can be performed with a high rate of success. If collateral blood supply to the spinal cord is maintained, occlusion of the intercostal arteries does not cause symptomatic malperfusion. However, if acute or chronic occlusion of the subclavian, lumbar or hypogastric arteries is present, likelihood of symptomatic malperfusion dramatically increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
0
17
0
2
Order By: Relevance
“…Additionally, previous reports have suggested that neurologic recovery with delayed paraplegia compared to immediate paraplegia has a more favorable outcome 7, 9, 1113 but small sample sizes make it difficult to draw definitive conclusions about the natural history of SCI after TEVAR. Moreover, few reports have focused on the long-term functional outcome of patients with SCI after TEVAR, and the prognostic implications of the degree and speed of functional recovery after SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous reports have suggested that neurologic recovery with delayed paraplegia compared to immediate paraplegia has a more favorable outcome 7, 9, 1113 but small sample sizes make it difficult to draw definitive conclusions about the natural history of SCI after TEVAR. Moreover, few reports have focused on the long-term functional outcome of patients with SCI after TEVAR, and the prognostic implications of the degree and speed of functional recovery after SCI.…”
Section: Introductionmentioning
confidence: 99%
“…B. karotidosubklavialer Bypass) erforderlich, um die Durchblutung der A. subclavia sinister wieder herzustellen [8]. Bekannt ist, dass durch die Implantation der Stentgrafts andere Zuflüsse zum Rücken-mark aus segmentalen Arterien (Interkostal-, Lumbal-, Vorderwurzel-und Hinterwurzelarterien) ebenfalls blockiert werden können und sich dadurch komplette oder inkomplette spinale Ischämien ereignen können (Risiko 4-7%) [5]. [1,10,11].…”
Section: Tevarunclassified
“…In diesen Fällen werden Verschlüsse und Scherverletzungen dissektiv veränderter oder auch durch den Stent überbrückter Gefäße vermutet, deren Kollateralversorgung im Myelon nicht sichergestellt werden kann [5]. Die Prognose spinaler Ischämien ist unabhängig von ihrer Auslö-sung grundsätzlich ungünstig, auch wenn selten Spontanremissionen vorkommen.…”
unclassified
“…Techniques of left subclavian artery transposition or left carotid to left subclavian artery bypass and preventive cerebrospinal fluid (CSF) drainage prior to TEVAR has been shown to reduce the incidence of SCI. Other endovascular techniques have been used to prevent SCI such as staged coverage of the TAAA or maintaining a flow through an unstented branch vessel that may be embolized at a later date .…”
mentioning
confidence: 99%